Knowing the Unknown: Exploring the inaccessible meaning through accessible past in Shahid Nadeem’s Aik Thi Nani - Dr. Sobia Mubarak, Asim Lodhi (Journal of Research in Humanities, 2020)
This paper claims that the South Asian Drama reflects on the traumatic event in objective history to reveal those truths which may develop an understanding that can help people of South Asia to come out of the trauma of colonialism. The understanding of the traumatic event becomes possible when trauma reappears ‘belatedly’ through literary language. Through the lens of Trauma Theory propounded by Cathy Caruth, this research maintains that the primary task of literature being produced in the post-colonial context is to engage with and reflect on the past to develop understanding about the traumatic event, revealing the hidden or unknown dimensions which have been unspeakable otherwise. Drawing on the philosophies of phenomenology, trauma theory and post-structuralism, I intend to establish that by engaging with the phenomenon of the actual traumatic event through theater, it becomes possible to explore the inaccessible meaning or truth. This meaning becomes accessible only for the present and not for good. It is a product of present consciousness. A dramatist writing in the post-colonial context feels committed to writing about these themes because the subjectivity of South Asians is traumatized due to the colonial past. The existence of the phantoms of the past can be witnessed in the shape of contemporary realities such as the biased curriculum, the dearth of intellectual endeavors, misrepresentation of history, and the politics of religious identities and double consciousness. In the present post-colonial context, a mere representation of these issues cannot be of any use to de-traumatize the people of South Asia. This study analyses that Shahid Nadeem’s play Aik Thi Nani does not simply highlight or represent the consequences of the traumatic event rather their texts seem to engage with the belated appearance of the trauma of colonization. Therefore, in the works of my primary dramatist, trauma is not dealt with as a clinical malady but a cultural trope which works as a vehicle of truth about the traumatic event in the past. This research concluded that the trauma of colonialism as a cultural trope is part of the individual and collective memory of the South Asian people and the solution lies in engaging with the past rather than eradicating it out of our lives.